2019
DOI: 10.3390/su11226359
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Change Characteristics of Nodes’ Heterogeneity in the Directed and Weighted Spatial Interaction Networks: Case Study within the Sixth Ring Road of Beijing, China

Abstract: Spatial heterogeneity patterns in cities are an essential topic in geographic research and urban planning. This paper analyzes the spatial heterogeneity of places and reflects on the urban structure in cites based on spatial interaction networks. To begin with, we constructed 24 sequentially directed and weighted spatial interaction networks (DWNs) on the basis of points of interest (POIs) and taxi GPS data in Beijing. Then, we merged 24 sequential networks into four clusters: early morning, morning, afternoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Based on the above research, to investigate the interaction patterns between urban structure and traffic flow, we used the spatial hotspot analysis method [18] and the complex network [16] analysis method to explore spatio-temporal hotspots [19][20][21] and studied the urban traffic flow network from the perspective of network centrality [22]. We divide the study area into fine-grained grids [23] to avoid administrative districts to fragment geographic entities and propose a new trajectory direction description field model.…”
Section: Related Workmentioning
confidence: 99%
“…Based on the above research, to investigate the interaction patterns between urban structure and traffic flow, we used the spatial hotspot analysis method [18] and the complex network [16] analysis method to explore spatio-temporal hotspots [19][20][21] and studied the urban traffic flow network from the perspective of network centrality [22]. We divide the study area into fine-grained grids [23] to avoid administrative districts to fragment geographic entities and propose a new trajectory direction description field model.…”
Section: Related Workmentioning
confidence: 99%
“…Big data overcome the shortcomings of traditional data to some extent [23,24], reflecting more accurate population movement in real time. Some scholars have made use of big data of population mobility to carry out researches on the intercity connection and urban network [6,7,[25][26][27][28][29]. For example, the paper uses Baidu migration big data to study the characteristics of the rich club of the population mobility network during the Spring Festival travel rush in China [30] and the multisource migration big data of Baidu, Tencent, and Qihoo to study the travel characteristics of the population during the Spring Festival travel rush in China [25].…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…Previous studies showed that there is a considerable variation at different hours and different days regarding the number of taxi pick-ups and drop-offs [17,18]. Therefore, we selected, separately, two groups of OD flows that appeared on weekdays and weekends.…”
Section: Spatio-temporal Patterns Of Urban Travelling Hotspotsmentioning
confidence: 99%
“…Some of them explored the spatial distributions of travels for diverse social activities [15] and the geographical characteristics of urban travel demand [16]. Apart from that, Yang et al evaluated the diverse popularity of places in the urban area by human travelling [17,18]. Other research focused on the spatio-temporal characteristics of urban travelling hotspots [2,19,20].…”
Section: Introductionmentioning
confidence: 99%